Proceedings of the 28th International Conference on Computational Linguistics 2020
DOI: 10.18653/v1/2020.coling-main.507
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Model for Aggregating Coreference Annotation in Crowdsourcing

Abstract: Coreference resolution is the task of identifying all mentions in a text that refer to the same real-world entity. Collecting sufficient labelled data from expert annotators to train a highperformance coreference resolution system is time-consuming and expensive. Crowdsourcing makes it possible to obtain the required amounts of data rapidly and cost-effectively. However, crowd-sourced labels can be noisy. To ensure high-quality data, it is crucial to infer the correct labels by aggregating the noisy labels. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…A number of models are developed to aggregate a higher-quality corpus from the crowdsourcing corpus (Raykar et al, 2010;Rodrigues et al, 2014a,b;Moreno et al, 2015), aiming to reduce the gap over the expert-annotated corpus. Recently, modeling the bias between the crowd annotators and the oracle experts has been demonstrated effectively (Nguyen et al, 2017;Simpson and Gurevych, 2019;Li et al, 2020), focusing on the label bias between the crowdsourcing annotations and gold-standard answers, regarding crowd-sourcing annotations as annotator-sensitive noises. do not hold crowdsourcing annotations as noisy labels, while regard them as ground-truths by the understanding of individual crowd annotators.…”
Section: Related Workmentioning
confidence: 99%
“…A number of models are developed to aggregate a higher-quality corpus from the crowdsourcing corpus (Raykar et al, 2010;Rodrigues et al, 2014a,b;Moreno et al, 2015), aiming to reduce the gap over the expert-annotated corpus. Recently, modeling the bias between the crowd annotators and the oracle experts has been demonstrated effectively (Nguyen et al, 2017;Simpson and Gurevych, 2019;Li et al, 2020), focusing on the label bias between the crowdsourcing annotations and gold-standard answers, regarding crowd-sourcing annotations as annotator-sensitive noises. do not hold crowdsourcing annotations as noisy labels, while regard them as ground-truths by the understanding of individual crowd annotators.…”
Section: Related Workmentioning
confidence: 99%
“…But in reality, different annotators have levels of expertise in different domains. It has been demonstrated that proactive learning is helpful for task allocation in crowdsourcing setting where the level of expertise varies from annotator to annotator (Donmez and Carbonell, 2010;Li et al, 2017Li et al, , 2019Li et al, , 2020b. Proactive learning is useful in modelling the annotator reliability which can used to assign the unlabelled instances to the best possible Before any annotation, Paladin estimates the proficiency of the annotators for each class by assigning the documents in the seed dataset to all annotators.…”
Section: Proactive Learningmentioning
confidence: 99%
“…Research in NLP has noticed the inherent disagreement and ambiguity in annotations since long ago (Poesio and Artstein, 2005;Zeman, 2010). Many previous works expose and learn from ambiguous, noisy annotations in coreference resolution (Poesio et al, 2008(Poesio et al, , 2019Li et al, 2020). Related research also exists in POS-tagging (Zeman, 2010;Plank et al, 2014Plank et al, , 2016, semantic frame disambiguation (Dumitrache et al, 2019), humorousness prediction (Simpson et al, 2019), etc.…”
Section: Related Workmentioning
confidence: 99%